Results of the Cologne Corona Surveillance (CoCoS) study - a cross-sectional study: survey data on risk factors of SARS-CoV-2 infection in adults - Oberste, Maximilian; Schnörch, Nadja; Shah-Hosseini, Kija; Asenova, Teodora; Dewald, Felix; Lehmann, Clara; Buess, Michael; Fätkenheuer, Gerd; Klein, Florian; Rosenberger, Kerstin Daniela; Kossow, Annelene; Neuhann, Florian; et al. (BMC public health, 2023)
The personal, environmental, and behavioral risk factors that play an important role in the spread of SARS-CoV-2 are still largely unclear. At the same time, there is limited evidence on the effectiveness of specific countermeasures for SARS-CoV-2. As a first approach to these questions, we use data from the Cologne Corona Surveillance (CoCoS) study, a large cross-sectional study conducted in Cologne, Germany, in June 2021.
Gesehen am 29.03.2023